(untitled) (Scientific journal of the Fergana State University, 2025)
This study explores gender differences in nonverbal communication by analyzing the varying use of gestures, facial expressions, spatial positioning, eye contact, and other nonverbal cues among men and women. Using a mixed-methods approach, observational and survey data were collected from a diverse group of participants to evaluate these nonverbal tendencies. Findings reveal that women typically exhibit greater expressiveness, engage in longer eye contact, and demonstrate a preference for closer physical proximity, while men tend to display more reserved body language and favor wider personal space. These insights contribute to a more nuanced understanding of gendered communication styles and their potential impact on social, professional, and cultural interactions.